Household dietary diversity and nutritional status of preschool children in semi-urban and rural communities of Umuahia South Local Government Area, Abia State, Nigeria - Okorie, Ijioma; Nwofia, Blessing K; Agina, Emeka K; Ekeowa, Nkemdilim J (World Nutrition, 2025)
BackgroundThe nutritional well-being of preschool children (2–4 years) is critical to achieving Sustainable Development Goal 2 (Zero Hunger).ObjectiveThe purpose of the study was to assess the household dietary diversity score (HDDS) and the nutritional outcomes of preschool children in Umuahia South Local Government Area (LGA), Abia State, Nigeria.MethodsA community-based cross-sectional study was conducted in six randomly selected communities in the LGA. Data were collected from mother–child pairs in 318 systematically sampled households. A semi-structured questionnaire was used to collect data on socio-demographics, HDDS, and individual dietary diversity score (IDDS) of preschool children. Children’s weight and height were measured and analysed using WHO Anthro software, based on WHO Child Growth Standards. Data were analysed using descriptive statistics (frequencies, percentages, means, and standard deviations) and Chi-square tests, with statistical significance set at p < 0.05.ResultsMost households were small (1–5 members; 64.5%), and had low income (< N70,000 per month; 66.4%). Most households (67.6%) and preschool children (52.8%) did not meet minimum dietary diversity (MDD) thresholds (≥6 food groups for households and ≥4 food groups for children). The prevalence of malnutrition among children was 25.5% for stunting, 7.9% for wasting, 15.7% for underweight, and 3.1% for overweight/obesity based on WHO growth standard z-scores. Stunting was significantly associated with household and IDDS, income, and maternal education (p < 0.05). Underweight was associated with household size and IDDS.ConclusionsMost of these preschool children did not meet MDD, and this was associated with high rates of stunting and underweight. Also, large household size and low income were strongly associated with underweight. Interventions to improve dietary diversity to enhance the nutritional outcomes of preschool children should be prioritized.